Calendar Life of Zn Batteries Based on Zn Anode with Zn Powder/Current Collector Structure. Issue 14 (19th February 2021) - Li, Qing; Wang, Yanbo; Mo, Funian; Wang, Donghong; Liang, Guojin; Zhao, Yuwei; Yang, Qi; Huang, Zhaodong; Zhi, Chunyi
Abstract: Zn foil is widely used for studying the stability and dendrite formation behavior of Zn anodes. The reported long cycling life of rechargeable Zn batteries (RZBs) is obtained by testing a battery immediately after its fabrication neglecting the aging effects. The cycling performance demonstrated cannot, however, have practical applications. Using Zn foil as both the working electrode and current collector will cause many problems when the battery is scaled up. A Zn powder (Zn‐P)/current collector configuration is more practical. In this work, the corrosion of the Zn‐P@Cu anode‐induced cell swelling is first quantitatively studied. During the aging process of the Zn‐P@Cu electrode, hydrogen forms on the surface of Cu and the Zn‐P dissolves resulting in morphological changes. These phenomena can be attributed to galvanic corrosion between Cu and Zn. To address this issue, tin with a higher overpotential for hydrogen generation is plated on Cu surface. The results indicate that hydrogen evolution is ameliorated. With a low NP ratio (mass) of 10:7, considerably better storage and cycling performance are achieved for Zn‐P@Cu//MnO2 . These results highlight the need to focus on the calendar life of RZBs and corrosion of the Zn anode. Abstract : A Zn powder (Zn‐P)/current collector configuration is more practical in the context of Zn anodes than the traditionally used Zn foil. A current collector is vital since galvanic corrosion happens within bimetallic systems. During the aging process of Zn‐P@Cu, hydrogen forms, Zn‐P dissolves, contact deteriorates, and the battery fails after storage. Introducing Sn coating with a high hydrogen generation overpotential can alleviate the galvanic corrosion and lead to a better cell storage performance.